Traction mechanics of the designed and developed segmented rubber track vehicle for Sepang peat terrain in Malaysia during turning motion: theoretical and experimental analysis - Rahman, Mohammed Ataur; Yahya, Azmi; Zohadie, Mohd.; Wan Ismail, Wan Ishak (Inderscience Enterprises Ltd., 2006)
The traction mechanics of the vehicle was developed based on the track-terrain interaction mechanism. The simulation results indicated that the vehicle with full payload turning on peat terrain should be turning 2m radius at least for the fulfilment of vehicle floatation ability; 4m radius or less for the fulfilment of vehicle turning ability; and at 4m radius at least for the fulfilment of vehicle turning stability. The vehicle was tested on the three different terrains: terrain type I, terrain type II, and terrain type III. The maximum percentage of tractive effort variation was found for terrain type I because of the lowest moisture content.